Stable isotopes and hydrogeochemical evolutions of groundwater from a typical seismic fault zone in the Mt. Lushan region, Eastern China - Bao, Zhicheng; Hu, Le; Xiao, Jian; Zha, Xiaohui; Lv, Jian; Zhao, Ying (Frontiers in Earth Science, 2023)
We analyzed the major chemical components, hydrogen (δD) and oxygen isotopes (δ18O), and tritium activity in groundwater from Jiujiang well number 2 (JJ2) as well as atmospheric precipitation and water from the Maweishui spring and Tianhuajing reservoir in the Mt. Lushan region, Eastern China. The results show that the water in JJ2 is of the HCO3-Ca·Mg type, with ionic components mainly arising from calcite and dolomite mineral dissolution. According to the δD and δ18O data, the groundwater of JJ2 mainly comes from atmospheric precipitation, and the recharge elevation is 143~159m. Results for tritium activity indicate that JJ2 is fed by both an ancient water supply and a new water supply within a period of 10 years. These results demonstrate that JJ2 has characteristics of both shallow and deep circulating water, which implies that aquifers involving two different recharge sources rise to the well surface via different circulation paths. That is exactly why JJ2 is tectonically sensitive and could display a remarkable gas radon anomaly before the Ruichang-Yangxin ML 5.0 earthquake in 2011. Our results also indicate that ascertain the hydrological characteristics and cycling process of groundwater are crucial for understanding the earthquake anomalies and judging whether a seismic groundwater monitoring well is reliable or not.